Experimental determining of time and temperature strength parameters on which calculations of fire resistance can be based - Bednarek, Z. (Journal of Civil Engineering and Management, 1995)
The author presents results of his own experiments for determining strength parameters of steel in thermal conditions of fire on which calculations of fire resistance can be based. The author suggests the calculation of the thermal strength parameters on the basis of noncoventional tensile test in thermal conditions described by the “time-temperatures” curve. Test bars were loaded with the constant force, presented as a steady stress level. The author also investigated the influence of various thermal conditions, described by some “time-temperature” curves, on strength parameters.Article in Lithuanian.Laiko ir temperatūros parametrų, taikomų skaičiuoti atsparumą ugniai, eksperimentinis nustatymasFirst Published Online: 26 Jul 2012